PERSEPSI DUNIA KERJA TERHADAP LULUSAN FRESH GRADUATE S1 MENGGUNAKAN MULTIDIMENSIONAL UNFOLDING (Studi Kasus: Dunia Usaha di Kabupaten Batang) - Adhyaksa, M. Atma; Rusgiyono, Agus (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2010)
Corporate perception of college graduates S1 fresh graduate is a viewpoint held by the world of work regarding the criteria considered in selecting candidates for most job applicants from graduates S1 fresh graduate based on his resume. Perceptions are reviewed based on the configuration of unfolding multidimensional mapping between business entities with the most preferred criteria in the selection process beginning college graduates S1 fresh graduate. Multidimensional unfolding was one of the techniques used in analyzing the proximity between objects is visualized in graphical form in which individuals and stimuli presented in one graph. Â The result is a grade point average, ability and suitability of computer applications course with the working position is most noticed by companies in selecting a job application letter from the college graduates S1 fresh graduate. Â Keywords: Corporate Perception, Fresh Graduate, Multidimensional Unfolding